Black propinquity in 21st century America - Lockett, Lorenza (Kansas State University, 2015)
There is considerable research on concepts of Blackness in America. Much of this research is conducted within a Eurocentric as opposed to an Afrocentric perspective. Social research has established that ideals, social norms, and values about Black minority groups may be shaped by dominant culture premises and that the dominant culture of any society can influence the attitudes, perceptions, and behaviors of minority group members coexisting within that culture. The White racial frame holds that over time a dominant cultural perspective in the U.S. has installed a positive orientation to “White” and whiteness and a strong negative orientation toward racial “others”, particularly toward Black Americans. The present research explores this phenomenon from an Afrocentric perspective, assessing propinquity preferences of non-native Immigrant and native-born American Blacks toward native-born Blacks. Utilizing data drawn from The National Survey on American Life 2001-2003 (Jackson, 2007) the study assessed the degree of Black propinquity (i.e., self-identified feelings of closeness and identity preferences with native-born Blacks) expressed within and between subsamples of native-born African American (n = 3,464) and non-native (chiefly Afro-Caribbean) Blacks (n = 1,118). More specifically, it hypothesized that native-born Blacks would display greater propinquity preferences than Immigrant Blacks for native-American Blacks depicted as more economically-challenged as well as socially affluent and elite; also, it expected they would report greater support for socially undesirable as well as socially desirable Blacks than would Immigrant Blacks. A series of hierarchical regression analyses modeled the unique and joint predictive variance of socio-demographic, socio-economic, and Black (derived) target characteristics within each Black subpopulation against the primary outcome variable (propinquity). Overall regression models for each Black group were highly similar in the proportion of explained variance (27% for native Blacks; 26% for Immigrant Blacks) and weighted contributions of three blocks of variables; derived variables for Black target characteristics contributed most of the total variance within each group. No statistically reliable differences for R score values were found between the two Black subpopulations on these derived variables. Findings are discussed in the context of the White racial frame perspective, secondary data methodology, and future research.
Keywords: Propinquity; Nearness; Social closeness; Blackness; Black identity; Closeness in feelings and image ideations; African American Studies (0296); Black Studies (0325); Ethnic Studies (0631)